Measuring financial development in India: A PCA approach - Sanjaya Kumar LENKA (Theoretical and Applied Economics, 2015)

(untitled)
Financial development is a multidimensional concept and its measurement is thorny for the researchers. A good measurement of financial development is decisive in evaluating the progress of financial sector development and understanding the corresponding impact on economic growth and poverty reduction. The study makes use of the PCA (Principal components analysis) to construct a financial depth index (IFD) that serves as a proxy variable of financial development position of the country. This paper used Indian time series data covering a period from 1980 to 2011(Index-1) and 1990-2011(Index-2) for measurement of two separate financial development index. This study gives insight for understanding various financial sector proxies as well as to enhance the knowledge of financial position of the country. The proposed index is easy to compute and comparable across countries.